ANALYSIS OF THE SYMBOL IN THE HISTORY OF PHILOSOPHY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the 21st century, the desire for integration and integrity of culture has led to the need for a close study of the symbol as a holistic and, at the same time, contradictory phenomenon, as a full-fledged instrument of relationships between subjects and objects of cultural space. The article provides a brief historical analysis of the emergence and development of the symbol as a phenomenon of the development of human culture.